Pengembangan Manajemen Pengelolaan Kelas Berbasis Teknologi Bagi Guru-Guru Sekolah Dasar - Margareta Oktavia Sumilat; Risal M. Merentek (Jurnal Ilmiah Wahana Pendidikan, 2022)
This community service activity offers a solution to improve the quality of education, it is necessary to improve and improve education, which is closely related to improving the quality of operational learning that takes place in the classroom. The implementation method is carried out in the form of: training, workshops and mentoring. The method used in training, workshops and mentoring is in the form of a cycle which is carried out in five stages, namely: the planning stage, the action stage, the observation stage, the reflection stage, and the follow-up stage. In completing the implementation of these activities, several tests and activities were carried out such as: preliminary and final tests, seminar activities in the form of lectures, demonstrations, simulations, and assignments. The success of teachers in implementing classroom management can be seen from the ability and seriousness of teachers in 1) Activities related to the creation and maintenance of optimal learning conditions, 2) Activities related to developing optimal learning conditions, 3) Activities to create a teaching and learning climate good, 4) Learning evaluation activities